2020
DOI: 10.1111/nmo.13851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the colonic response to bisacodyl in children with treatment‐refractory constipation

Abstract: Background Colonic manometry with intraluminal bisacodyl infusion can be used to assess colonic neuromuscular function in children with treatment‐refractory constipation. If bisacodyl does not induce high‐amplitude propagating contractions (HAPCs), this can be an indication for surgical intervention. A detailed characterization of the colonic response to intraluminal bisacodyl in children with constipation may help to inform clinical interpretation of colonic manometry studies. Methods Studies were performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…We used water perfused catheters for the ability to clip them with an Endo clip to the colonic mucosa to stay in place after placement. Previous multicenter studies did not show major differences between solid state vs water perfused catheters in the assessment of HAPC 8 . None of the patients had complications during or after the study.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…We used water perfused catheters for the ability to clip them with an Endo clip to the colonic mucosa to stay in place after placement. Previous multicenter studies did not show major differences between solid state vs water perfused catheters in the assessment of HAPC 8 . None of the patients had complications during or after the study.…”
Section: Methodsmentioning
confidence: 68%
“…6 HAPC is defined as high amplitude contractions of 65 mmHg or more, propagating at least 30 cm distally for at least 10 s, although slightly varying definitions have been described in literature. 5,[7][8][9] A colonic manometry study is performed using published guidelines (ANMS and NASPGHAN guidelines). 5 Measurements during fasting, after a meal, and after colonic stimulation by stimulants to induce HAPC are done to evaluate colonic motility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bisacodyl can elicit high-amplitude propagating contractions and therefore helps to distinguish between patients with normal or impaired colonic propulsion [46,47]. A recent study including 165 children with treatment-refractory constipation found that in 93% of children intraluminal administration of bisacodyl induced highamplitude propagating contractions, confirming the stimulating effect of bisacodyl on the colonic peristalsis in children [48]. However, good-quality evidence for the efficacy and safety of bisacodyl in children with FC is lacking [27].…”
Section: Diphenylmethanesmentioning
confidence: 99%